The prevalence of sarcopenia and risk factors in the older adult in China: a systematic review and meta-analysis - Meng, Shilong; He, Xiaomin; Fu, Xinlei; Zhang, Xu; Tong, Minghao; Li, Wei; Zhang, Wei; Shi, Xiaolin; Liu, Kang (Frontiers in Public Health, 2024)
Background: Understanding the epidemiological information of a certain disease is the first step in related prevention and control work. This article aims to understand the prevalence and associated risk factors of sarcopenia among the elderly (≥60 years old) in China and to provide an evidence-based basis for early identification, management, and prevention of sarcopenia patients. Methods: We searched seven databases: CNKI, Wanfang, VIP, PubMed, Web of Science, Embase, and Cochrane Library databases from the establishment of the database until January 31, 2024. The Quality evaluation criteria of cross-sectional studies recommended by the Agency for Healthcare Research and Quality (AHRQ) were used for literature quality evaluation. Stata 18.0 software was used for statistical analysis. Results: We finally included 45 studies, involving a total of 37,571 cases. After statistical analysis, we found that the prevalence of sarcopenia among the elderly in China was 20.7% [95% CI (18.3%, 23.0%)]. The results of subgroup analysis suggest that: ① According to gender, the prevalence rate of sarcopenia in women (21.6%) is higher than that in men (19.2%); ② According to age, the prevalence rate of elderly people aged ≥80 (45.4%) was the highest, followed by 70-79 (27.2%) and 60-69 (15.7%). ③ According to region, the prevalence rate of the elderly in the south (21.7%) is higher than that in the north (19.0%); ④ According to the time of publication, the prevalence of sarcopenia among the elderly in China has increased (from 19.2% in 2014-2018 to 21.4% in 2019-2024); ⑤ According to the diagnostic criteria, the detection rate of AWGS(2019) is higher than that of AWGS(2014) (24.5% vs 19.3%). Finally, aging, low BMI, low leg circumference, smoking, depression, osteoporosis, malnutrition, and malnutrition risk are all risk factors for sarcopenia among the elderly in China. Conclusion: The prevalence of sarcopenia in the elderly in China was higher (20.7%)， which should be paid attention to by relevant health authorities.